(untitled) (Journal of the College of Basic Education, 2023)
Modern philosophy has changed the way Western civilization looks at the world, after it was specificIn the religious and theological perspectives and perceptions that prevailed in Europe in the Middle Ages, especially inThe framework of the old problematic, by which we mean the relation of awareness to the world* or what is called the relation of thoughtIndeed.Heidegger says about the era of modern philosophy that it began ((at the moment in whichMan to return to himself from whence he is that being who is represented by returning all things to himselfAs a higher ruling)) 1, meaning that the understanding of the world or reality begins with man as something thinking orself-aware. This tendency has flourished in contemplation or thinking as a result of the collapse of the paradigmAl-Irshady (Paradigm) ** Al-Quraustu in thinking and the emergence of what was called the tendencyHumanism *** seeking man’s domination over nature and the world.It was one of the most important factors that made the modern era different from the medieval era.It is ((the shrinking of the Church and the increase in the authority of science)) 2. This led to the liberation of man from the burden ofHistory, heritage, theology, and the emergence of self- and individual control 3 on which the method ofIts existence and truth. All philosophical systems in the modern period, in all their features, represent or expressOn the self-practice of a variety of acts of unification, that is, the unification between consciousness and the world mediated by the principle ofThe correspondence between the mind and the world, which is the goal of European modernity. man in the modern eraHe became a visualizer of the world and represented it rather than questioning it, visualizing its assets as objects.Standing in front of himself, it is the thinking self according to Descartes, the founder of modern philosophy ((and the owner of the spiritMuqadamah who made the self the correcting foundation and the new beginning for every new philosophy that wants toIt is founded)) 4 in the words of the German philosopher Hegel. As Spino R has lost the essence of autonomyIt is characterized by thought and extension, as the mind and body are one and not two different things as they are atDescartes, the mind looks at it through the adjective of thought, while the body is seen through the adjectiveThe extension. As for the German philosopher Leibniz, he counted the self as a monad **** as one.